Evaluation of the potassium channel tracer [18F]3F4AP in rhesus macaques. Issue 7 (July 2021) - Guehl, Nicolas J; Ramos-Torres, Karla M; Linnman, Clas; Moon, Sung-Hyun; Dhaynaut, Maeva; Wilks, Moses Q; Han, Paul K; Ma, Chao; Neelamegam, Ramesh; Zhou, Yu-Peng; Popko, Brian; Correia, John A; et al.
Demyelination causes slowed or failed neuronal conduction and is a driver of disability in multiple sclerosis and other neurological diseases. Currently, the gold standard for imaging demyelination is MRI, but despite its high spatial resolution and sensitivity to demyelinated lesions, it remains challenging to obtain specific and quantitative measures of molecular changes involved in demyelination. To understand the contribution of demyelination in different diseases and to assess the efficacy of myelin-repair therapies, it is critical to develop new in vivo imaging tools sensitive to changes induced by demyelination. Upon demyelination, axonal K + channels, normally located underneath the myelin sheath, become exposed and increase in expression, causing impaired conduction. Here, we investigate the properties of the K + channel PET tracer [ 18 F]3F4AP in primates and its sensitivity to a focal brain injury that occurred three years prior to imaging. [ 18 F]3F4AP exhibited favorable properties for brain imaging including high brain penetration, high metabolic stability, high plasma availability, high reproducibility, high specificity, and fast kinetics. [ 18 F]3F4AP showed preferential binding in areas of low myelin content as well as in the previously injured area. Sensitivity of [ 18 F]3F4AP for the focal brain injury was higher than [ 18 F]FDG, [ 11 C]PiB, and [ 11 C]PBR28, and compared favorably to currently used MRI methods.